Swap70b acts downstream of Wnt11 signalling to regulate zebrafish convergence and extension cell movements - Xu, Xiaoou (2015)
During vertebrate gastrulation, convergence and extension (CE) cell movements narrow the body axis medial-laterally (convergence) and extend it anterior-posteriorly (extension). In zebrafish, Wnt11 (silberblick) and Wnt5b (pipetail) mutants exhibited widening and shortening of the body axes characteristic for CE cell movements defects during gastrulation. It was subsequently reported that Wnt signalling resulted in activation of Rho GTPases and rearrangements of the F-actin cytoskeleton, establishing that CE cell movements are regulated through the non canonical Wnt/PCP pathway. Rho GTPases are activated by guanine nucleotide exchange factors (GEFs) and it was recently found that Def6a, a GEF for Rac1, Cdc42, and RhoA, was the downstream target of Wnt5b signalling. In this thesis, morpholino-mediated knockdown of gene expression in conjunction with phenotypic rescue experiments revealed that Swap70b, a GEF protein closely related to Def6a, functions downstream of Wnt11. Swap70b morphants exhibited broader and shorter body axis with no apparent defect in cell fate specification, and ectopic Swap70b expression robustly rescued wnt11 morphants, establishing Swap70b as a novel member of the non-canonical Wnt/PCP pathway downstream of Wnt11. The following phenotypic rescue experiments demonstrated that Swap70b and Def6a execute both distinct and overlapping functions in the modulation of CE cell movements. In addition, as previously shown for Wnt11 (silberblick) and Wnt5b (pipetail) double mutants, Swap70b and Def6a double mutant morphants exhibited a more severe CE cell movement defect, suggesting that Swap70b and Def6a delineate Wnt11 and Wnt5b signalling pathways.